Myristic Acid Coated Protein Immobilised Mesoporous Silica Particles as pH Induced Oral Delivery System for the Delivery of Biomolecules - Vivek Trivedi; Ruchir Bhomia; John C Mitchell (MDPI AG, 2019)
Solid core drug delivery systems (SCDDS) were prepared for the oral delivery of biomolecules using mesoporous silica as core, bovine haemoglobin (bHb) as model drug and supercritical fluid (SCF) processing as encapsulation technique. The use of organic solvents or harsh processing conditions in the development of drug delivery systems for biomolecules can be detrimental for the structural integrity of the molecule. Hence, the coating on protein-immobilised particles was performed via supercritical carbon dioxide (scCO2) processing at a temperature lower than the melting point of myristic acid (MA) to avoid any thermal degradation of bHb. The SCDDS were prepared by bHb immobilisation on mesoporous silica followed by myristic acid (MA) coating at 43 °C and 100 bar in scCO2. bHb-immobilised silica particles were also coated via solvent evaporation (SE) to compare the protein release with scCO2 processed formulations. In both cases, MA coating provided required enteric protection and restricted the bHb release for the first two hours in simulated gastric fluid (SGF). The protein release was immediate upon the change of media to simulated intestinal fluid (SIF), reaching 70% within three hours. The release from SCF processed samples was slower than SE formulations, indicating superior surface coverage of MA on particles in comparison to the SE method. Most importantly, the protein conformation remained unchanged after the release from SCDDS as confirmed by circular dichroism. This study clearly demonstrates that the approach involving protein immobilisation on silica and scCO2 assisted melt-coating method can protect biomolecules from gastric environment and provide the required release of a biologic in intestine without any untoward effects on protein conformation during processing or after release.